PEMBELAJARAN BERBASIS CRT DENGAN MODEL PROBLEM BASED LEARNING PADA MATA PELAJARAN PKN UNTUK MENINGKATKAN HASIL BELAJAR SISWA SDN PANDANWANGI 3 - Rahayu, Meirna; Thohir, M. Anas; Amzah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the use of the CRT approach with the Problem-Based Learning model in Civics subjects with the help of flashcards that raise the theme of how diversity can affect the learning outcomes of grade 2 students at SDN Pandanwangi 3. This research method uses classroom action research (PTK) which consists of two cycles. This research uses qualitative and quantitative descriptive methods. Data were collected through observation, interviews, documentation, and evaluation of learning outcomes. The results showed a significant increase in students' average scores, from 82.43 in the pre-cycle to 89.29 in cycle I and 97.86 in cycle II. The number of student completions also increased, with 78.57% completed in the pre-cycle, 100% in cycle I, and 100% in cycle II. This shows that the application of the CRT approach with the PBL model assisted by flashcards is very suitable for improving student learning outcomes. In conclusion, the CRT approach in PBL assisted by diversity flash cards makes a significant contribution to enriching the understanding of inclusive learning that is student-centered and relevant to cultural diversity. This research is expected to contribute to improving the quality of basic education by prioritizing cultural diversity in the learning process.